2010
DOI: 10.1186/1471-230x-10-16
|View full text |Cite
|
Sign up to set email alerts
|

A candidate probiotic with unfavourable effects in subjects with irritable bowel syndrome: a randomised controlled trial

Abstract: BackgroundSome probiotics have shown efficacy for patients with irritable bowel syndrome (IBS). Lactobacillus (L.) plantarum MF1298 was found to have the best in vitro probiotic properties of 22 strains of lactobacilli. The aim of this study was to investigate the symptomatic effect of L. plantarum MF1298 in subjects with IBS. Primary outcome was treatment preference and secondary outcomes were number of weeks with satisfactory relief of symptoms and IBS sum score.MethodsThe design was a randomised double blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 25 publications
0
71
0
2
Order By: Relevance
“…Two frequently included papers reported studies in children. 49,50 Two were placebo controlled but single-blinded studies, 33,51 one combined acupuncture with probiotic treatment, 46 and one 32 reported microbiota changes from a probiotic trial published before 52 which was already included in our list.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two frequently included papers reported studies in children. 49,50 Two were placebo controlled but single-blinded studies, 33,51 one combined acupuncture with probiotic treatment, 46 and one 32 reported microbiota changes from a probiotic trial published before 52 which was already included in our list.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the bacterial strains studied, the heterogeneity continued: 6 studies used Lactobacillus plantagus, 52,85,89,105,106,108 however of different origin and subspecies; some were nutritional supplements and some were developed as drugs. Other lactobacilli strains were used only in single trials, such as Lactobacillus brevi, 90 L. acidophilus, 56,100 Lactobacillus reuteri, 103 Lactobacillus rhamnosus GG, 107 and Lactobacillus casei (CLR35).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, in other study Lactobacillus plantarum MF1298 species had aggravated IBS symptom score, and this means not all strains with in vitro demonstrated probiotics actually showed therapeutic effects on the in vivo condition. 9 To date, clinical research with probiotics in IBS patients suffered from methodological limitations such as differences in study design, type of probiotics administered, and outcome parameters. Furthermore, previous studies frequently used subject endpoints and included heterogeneous patient populations.…”
Section: Commentsmentioning
confidence: 99%
“…Similarly, because probiotics potentially modulate a number of the pathophysiological mechanisms involved in IBS, they are usually given to all subtypes of the condition both in the clinical setting as well as in therapeutic trials. There have been twenty-eight controlled trials assessing the efficacy of probiotics in adults suffering from IBS with twenty (71 %) showing a positive effect (43,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75) , seven showing no effect (43,(76)(77)(78)(79)(80)(81) and one leading to a deterioration of symptoms (82) . In addition, four trials in children all gave positive results (83)(84)(85)(86) .…”
Section: Treating Irritable Bowel Syndrome With Probioticsmentioning
confidence: 99%